Carrying Capacity Assessment - An Essential Tool for Sustainable Tourism Development in Coastal Areas of Albania - Pasko, Genci (European Journal of Economics and Business Studies, 2016)
Like in many Mediterranean countries, the coastal areas in Albania are recognised among the country’s great assets both from the development and environmental point of view. Their scenic beauty, favourable climate, diversity of ecosystems, rich cultural and historical heritage make them excellent resources for the development of tourism, which is recognised as one of most important sector contributing to country’s national long-term growth. During the last twenty years, the coastal areas in Albania have attracted the major part of tourism investments, which due to the lack of legislation, urban planning and institutional capacity for sustainable development, have been spontaneous and have negatively affected the sustainable use of natural recourses. Thus, the proper planning and implementation of sustainable tourism development model together with the assessment of tourism carrying capacity, take a paramount importance for sustainable development of the coastal resources. Yet such assessment in Albania is not considered part of integrated planning and management of the coastal areas, therefore the carrying capacity assessment (CCA) should be considered an extremely important tool that should be used during the course of drafting policies and development plans for coastal areas. The CCA should not only be considered as a concept, or scientific calculation that shows the precise number of tourists for a particular area. Instead, it should be used as a flexible management tool for sustainable development of tourism allowing for optimum level of capacity in a certain area. Carrying capacities should also be considered an integral part of defining development scenarios for a given area in order to ensure a harmonised and sustainable development for the future. This process should be more effective if it develops in sympathy with the nature and character of costal environment, tourist needs and local population’s expectation for tourism development. This article presents the necessity of assessing and applying the CCA concept during the course of developing various tourism development models of coastal areas, with a a strong focus at application of sustainable tourism development scenario.
Keywords: Coastal areas, carrying capacity, sustainable tourism, tourism development scenarios